PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA SCRAPBOOK PADA SISWA KELAS X3 SMAN MUMBULSARI JEMBER - Rizqi Nur Hidayah; Astri Widyaruli Anggraeni; Maulida Safitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and describe the implementation of scrapbook media to determine students’ abilities in writing poetry. This research employed a Classroom Action Research (CAR) approach based on Kurt Lewin’s model, which consists of four main stages: planning, action, observation, and reflection. The participants of this study were 35 students from class X3 at SMAN Mumbulsari Jember. Data were collected through written tests, observations, and documentation.The findings indicate that the use of scrapbook media has a significant effect on improving students’ poetry writing skills. The average score of students in the pre-cycle was 71.6 (moderate category), which increased to 76.23 (high category) in Cycle I, and further improved to 91.06 (very high category) in Cycle II. In addition to enhancing learning outcomes, the application of the model and media also contributed to improvements in students’ creativity, motivation, self-confidence, and participation during the poetry writing learning process.